Islam dan Indonesia Menurut KH Zaini Mun'im: Wawasan Tentang Islam Nusantara - Suib, M. Syaiful (JURNAL AT-TURAS, 2018)
This paper examines Islam Nusantara which is considered as a form of local wisdom Indonesia and the combined value of Islamic theological values of local traditions, culture and customs in the country. Islam Nusantara, he said, is the typical style of Indonesian Islam. There are three main factors that accelerate the process of Islamization of the archipelago, one of which is the resilience of Islam that accommodate local values that do not conflict with the teachings of Islam. Insights and ideas keindonesiaan promoted by KH Zaini Mun'im about the problematics of propaganda Islamiyah, a similarity to Islam Nusantara, according to him, there are several factors which the problems of propaganda to the public which were related to propaganda material. According to him there are two kinds, namely the first; masyru material '(prescribed) such as faith, worship and discipline society. Second; ma'ruf means all actions that are useful and well-regarded, but not against the teachings of Islam, even can be done / done by the community, the opposite of evil. Panca awareness is also emphasized to the students his thoughts and insights about the importance of social and community life in the shadow of the NKRI.